The Effect Of Pre - Treatment Followed By Cryorolling On The Microstructures, Mechanical Properties And Corrosion Behaviour Of Al 5052 Alloy - Norazman, Muhammad Anas (2017)
This research was aimed to study the effect of different pre-heat treatment on cryorolled Al 5052 alloy. Two types of pre-treatments; without pre-treatment, annealing (150°C, 200°C, 250°C, 300°C and 350°C) and solution treatment (480°C, 510°C and 540°C) were selected to study the effect of pre-heat treatment on the properties of cryorolled Al 5052 alloy. Al 5052 alloys were heated at various pre-heat treatments process before cryorolling. Then, the Al 5052 alloys were dipped in liquid nitrogen and rolled at cryogenic temperature (cryorolling) at 30% thickness reduction. The Al 5052 alloy also was cold rolled at the 30% thickness reduction for comparison. The details of microstructural characteristics, physical properties, mechanical properties and corrosion behaviour of Al 5052 alloy were investigated using optical microscope (OM), scanning electron microscope (SEM), electron back scattered diffraction (EBSD), transmission electron microscope (TEM), X-ray diffraction (XRD), Vicker microhardness, Instron tensile test and potentiodynamic polarization test. The optical micrograph revealed that the grains are elongated along the rolling direction and the cryorolled samples showed higher grain aspect ratio compared to cold rolled. The grain aspect ratio increases with pre-heat treatment temperatures for both pre-heat treatment and achieved the highest aspect ratio at 300°C for pre-annealed and 540°C for pre-solution treated. The structure of cryorolled sample for both pre-heat treatment samples showed high density of dislocations and formation of submicron-sized grains. The mechanical properties showed that the cryorolled sample pre-annealed at 300°C exhibited the highest hardness, yield and ultimate tensile strength values with improvement of 17.3%, 13% and 15%, respectively, compared to non pre-treatment cryorolled sample. In contrast, the cryorolled sample pre-solution treated at 540°C exhibited the highest hardness, yield and ultimate tensile strength values with improvement of 13.6%, 7.1% and 4.8%, respectively, compared to non pre-treatment cryorolled sample. The cryorolled sample pre-annealed at 300°C and cryorolled sample pre-solution treated sample at 540°C exhibited the highest corrosion resistance due to lowest corrosion current, Icorr and corrosion rate values and more positive value of corrosion potential, Ecorr. The cryorolled sample pre-annealed at 300°C displayed an excellent physical, mechanical and corrosion properties compared to other samples. nano-composites are higher than UnF SiR/EPDM.